Application of Listening Team Learning Models in Improving Sociological Learning Outcomes - Suparman; Putriyani Samsul (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2021)
The main problem of research is whether the application of the listening team learning model can improve the sociology learning outcomes of the material values and social norms in class X students of Madrasah Aliyah Muhammadiyah Enrekang. This research is a Classroom Action Research (PTK) which is divided into two cycles with 4 stages, namely: planning, acting, observing, and reflecting repeatedly. This research was conducted at Madrasah Aliyah Muhammadiyah Enrekang. The object of the research was the students of class X Madrasah Aliyah Muhammadiyah Enrekang for the 2019/2020 academic year with a total of 20 students, consisting of 7 male students and 13 female students. The results showed that: 1) Sociology learning outcomes increased through the listening team learning model from the first cycle in the category with a very low score of 15%, a low score of 55%, and a moderate score of 30%. Sociology learning outcomes in cycle II are in the category of medium score 60% and high score 25%, and very high score 15%. 2) The results of the qualitative analysis show that there are changes that occur in students' attitudes during the learning process by the results of observations, namely the application of the listening team learning model on material values and social norms can improve student learning outcomes, student interest in learning and can increase student attendance.